Eye of the future: Unlocking the potential utilization of hydrogels in intraocular lenses - Hao Wu; Jiale Wang; Wenhui Fan; Qi Zhong; Rongyue Xue; Siyu Li; Zongming Song; Ye Tao (Wiley, 2024)
Abstract Hydrogels are distinguished by their exceptional ability to absorb and retain large volumes of water within their complex three‐dimensional polymer networks, which is advantageous for the development of intraocular lenses (IOLs). Their innate hydrophilicity offers an optimal substrate for the fabrication of IOLs that simulate the natural lens' accommodation, thereby reducing irritation and facilitating healing after surgery. The swelling and water retention characteristics of hydrogels contribute to their notable biocompatibility and versatile mechanical properties. However, the clinical application of hydrogels faces challenges, including managing potential adverse postimplantation effects. Rigorous research is essential to ascertain the safety and effectiveness of hydrogels. This review systematically examines the prospects and constraints of hydrogels as innovative materials for IOLs. Our comprehensive analysis examines their inherent properties, various classification strategies, cross‐linking processes, and sensitivity to external stimuli. Additionally, we thoroughly evaluate their interactions with ocular tissues, underscoring the potential for hydrogels to be refined into seamless and biologically integrated visual aids. We also discuss the anticipated technological progress and clinical uses of hydrogels in IOL manufacturing. With ongoing technological advancements, the promise of hydrogels is poised to evolve from concept to clinical reality, marking a significant leap forward in ophthalmology characterized by improved patient comfort, enhanced functionality, and reliable safety.